Uveal melanomas express vascular endothelial growth factor and basic fibroblast growth factor and support endothelial cell growth. Issue 4 (1st April 2002) - Boyd, S R; Tan, D S W; de Souza, L; Neale, M H; Myatt, N E; Alexander, R A; Robb, M; Hungerford, J L; Cree, I A
Abstract : Background: Tumour microvascularity is a significant determinant of prognosis for a large number of different tumours, including uveal melanoma. The development of blood vessels within these and other tumours is partly controlled by soluble pro-angiogenic cytokines, of which basic fibroblast growth factor (bFGF) and vascular endothelial growth factor-A (VEGF) are the best described. Methods: Because VEGF has been inconsistently found within uveal melanomas and bFGF is described as an autocrine growth factor in cutaneous melanoma, the authors looked at the expression of these cytokines in uveal melanomas using immunohistochemistry and reverse transcriptase polymerase chain reaction (RT-PCR). The cross talk between uveal melanoma cells and endothelial cells was then assessed in an in vitro co-culture model. Results: While most tumour cells expressed bFGF at the protein level by immunohistochemistry (89%), relatively few (22%) expressed VEGF, and this was of limited extent. All 20 tumours tested by RT-PCR contained mRNA for both bFGF and VEGF. Co-culture experiments using an ATP based bioassay showed that uveal melanomas could support the growth of a rat brain endothelial cell line (GPNT) and human umbilical vein endothelial cells (HUVEC), and that this could be modulated by cytokines and anti-cytokine antibodies. Conclusion: These results suggest that angiogenesis within uveal melanoma may be the result of a complex interplay between endothelial and tumour cells, and that bFGF and VEGF could play a part.